The Evaluation of The Founding Program of Badminton Clubs Aged 10-11 Years in Semarang City (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The research objectives were: (1) To evaluate the antecedents which include background, founding program, availability and feasibility of facilities and infrastructure, government and community support, availability of human resources, coach’s status, the acceptance of the athletes in PB Pendowo, PB Sehat, and PB Hamas, (2) To evaluate the transaction includes a program of exercise, coordination, and welfare, (3) To evaluate the outcomes, athletes' achievements. The type of this study was qualitative research using the Countenence (stake) evaluation. This study concluded that: (1) the antecedent of the founding program badminton clubs in the Semarang City to promote athletes aged 10-11 years in Semarang City, adequate facilities and infrastructure, the government supports, human resources were available, coach’s status and athlete acceptance goes well, (2) transactions involving founding programs do not based on the existing standards, coordination has been going well, welfare was not good enough, (3) outcomes of athletes had achieved good results and had increased from 2014 to 2017.